2013
DOI: 10.1103/physreva.88.043806
|View full text |Cite
|
Sign up to set email alerts
|

Input-output theory for waveguide QED with an ensemble of inhomogeneous atoms

Abstract: We study the collective effects that emerge in waveguide quantum electrodynamics where several (artificial) atoms are coupled to a one-dimensional superconducting transmission line. Since single microwave photons can travel without loss for a long distance along the line, real and virtual photons emitted by one atom can be reabsorbed or scattered by a second atom. Depending on the distance between the atoms, this collective effect can lead to super-and subradiance or to a coherent exchangetype interaction betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
311
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(320 citation statements)
references
References 53 publications
7
311
0
2
Order By: Relevance
“…In particular it has been discussed how photonic bandgap materials can be used to preserve the maximally symmetric entangled state [30,31] . Also, it has been shown that symmetrical state can be easily realized considering two superconducting qubits in 1-D trasmission line, where the photon-mediated interaction between the two artificial atoms leads to correlated states [32,33]. The interaction energy between the two atoms can be obtained using the resolvent formalism: the discrete level energies are given by the poles of the resolvent [34].…”
Section: The Modelmentioning
confidence: 99%
“…In particular it has been discussed how photonic bandgap materials can be used to preserve the maximally symmetric entangled state [30,31] . Also, it has been shown that symmetrical state can be easily realized considering two superconducting qubits in 1-D trasmission line, where the photon-mediated interaction between the two artificial atoms leads to correlated states [32,33]. The interaction energy between the two atoms can be obtained using the resolvent formalism: the discrete level energies are given by the poles of the resolvent [34].…”
Section: The Modelmentioning
confidence: 99%
“…(1) without any approximation. The theoretical framework is built upon methods developed for electrons scattered by magnetic impurities in condensed matter physics [2,3] as well as recent progress in one-dimensional waveguide quantum electrodynamics [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Although we illustrate the theory based on single photons, the framework is fundamentally compatible with and can be extended to multi-photons.…”
mentioning
confidence: 99%
“…In the quantum limit, efforts to build many-qubit systems blur the border between circuit quantum electrodynamics and metamaterials [5][6][7][8] while even the classical case holds a multitude of interesting and yet unexplored possibilities. Implementations of these structures, for instance in the form of parametric amplifiers 9 , have already attracted a great deal of attention and continue to do so as the field of superconducting metamaterials evolves.…”
mentioning
confidence: 99%